Disclosure of Whistleblowing Intent: Evidence from Accountants (Third Sector Social Economic Review, 2026)
Accounting fraud and financial reporting manipulations are among the unethical practices that undermine institutional trust and directly threaten the public interest. Whistleblowing is widely regarded as one of the most effective internal control mechanisms for detecting such fraudulent activities. The aim of this study is to explain the intention of dependent accountants to report significant accounting fraud and to examine the determinants of this intention within the framework of the Theory of Planned Behavior (TPB). In addition, the components of the Fraud Triangle (pressure/incentive, opportunity, and rationalization) were integrated into the model in order to develop a more comprehensive explanatory framework. The data were collected through a survey from 410 dependent accountants working under employment contracts across Türkiye. Measurement and structural model analyses were conducted using the SmartPLS 4.1.0.6 software package. The findings indicate that attitude toward whistleblowing and perceived subjective norms have strong and statistically significant effects on whistleblowing intention. In particular, attitude was identified as the most powerful predictor of whistleblowing intention. In contrast, perceived behavioral control was not found to have a significant effect on intention. Regarding the Fraud Triangle components, the results reveal that pressure/incentive significantly influences subjective norms, rationalization significantly affects attitude toward whistleblowing, and opportunity significantly impacts perceived behavioral control. Furthermore, the findings demonstrate that the whistleblowing intentions of dependent accountants are primarily shaped by social expectations, ethical evaluations, and professional values rather than purely individual considerations.
Keywords: Whistleblowing; Dependent Accountants; Audit; Fraud Triangle; Theory of Planned Behavior